Entrepreneurial Interest in Product Innovation-based Organic Processed Food in SMEs in Malang, Indonesia - Sri Muljaningsih (Department of Management, Faculty of Economics and Business, Brawijaya University, 2015)
The underlying reason for conducting the study is need for organic processed food. Producing innovative organic processed food is not an easy task since it requires creativity. The statement of the problem is how to create entrepreneurial interest to produce organic processed food. The study is a qualitative study of which purpose is to describe organic processed food SMEs behavior. There are 7 (seven) informants involved in the study. The setting of the study is SMEs in “Lily go to organic Group” community in Malang, Indonesia. Variables of entrepreneurial interest in organic processed food involve attitude, subjective norms and perceived behavioral control. The findings show that creativity influences entrepreneurial interest in organic processed food and it results in creativity. Creativity is also the result of spiritual entrepreneurship that takes understanding towards organic processed food material into consideration. In addition, Lily Group members also take time, capital, raw materials and marketing into account. Another finding reveals that sincerity and strong determination facilitates organic processed food entrepreneurs to work their best. Such determination needs reinforcement from other related party so that the product is accepted by customers.